Spondyloarthritis-Related Autoimmune Aortitis Complicated by Severe Aortic Regurgitation: The Importance of Multimodality Imaging Approach. (January 2019) - Chi, Wai Kin; Tse, Gary; Choi, Paul; Kam, Kevin K.H.; Tam, Lydia; Lee, Alex Pui Wai; Tam, Lai Shan
Abstract : Supplemental Digital Content is available in the text.